Rare genetic variation in UNC13A may modify survival in amyotrophic lateral sclerosis. Issue 7 (16th November 2016) - Gaastra, Benjamin; Shatunov, Aleksey; Pulit, Sara; Jones, Ashley R.; Sproviero, William; Gillett, Alexandra; Chen, Zhongbo; Kirby, Janine; Fogh, Isabella; Powell, John F.; Leigh, P. Nigel; Morrison, Karen E.; et al.
Abstract: Our objective was to identify whether rare genetic variation in amyotrophic lateral sclerosis (ALS) candidate survival genes modifies ALS survival. Candidate genes were selected based on evidence for modifying ALS survival. Each tail of the extreme 1.5% of survival was selected from the UK MND DNA Bank and all samples available underwent whole genome sequencing. A replication set from the Netherlands was used for validation. Sequences of candidate survival genes were extracted and variants passing quality control with a minor allele frequency ≤0.05 were selected for association testing. Analysis was by burden testing using SKAT. Candidate survival genes UNC13A, KIFAP3, and EPHA4 were tested for association in a UK sample comprising 25 short survivors and 25 long survivors. Results showed that only SNVs in UNC13A were associated with survival ( p = 6.57 × 10 −3 ). SNV rs10419420:G > A was found exclusively in long survivors (3/25) and rs4808092:G > A exclusively in short survivors (4/25). These findings were not replicated in a Dutch sample. In conclusion, population specific rare variants of UNC13A may modulate survival in ALS.